Penerapan Cognitive Behavior Theraphy (CBT) Pada Remaja Yang Mengalami Kecanduan Game Online Di SMP 6 Kota Gorontalo - Meta Puspita Dewi Antu Zees; Hendrik Prayitno Luawo (Poltekkes Kemenkes Gorontalo, 2022)
Online Game Addiction is a form of addiction caused by internet technology or better known as internet addiction. One alternative that can deal with online game addiction is Cognitive Behavior Therapy. The purpose of this study is to apply CBT in reducing addiction to online games at SMP Negeri 6 Gorontalo City. the method used in the implementation of this case study is descriptive, then the results are presented in narrative form and described in Cognitive Behavior Therapy (CBT) for adolescents who are addicted to online games in SMP Negeri 6 Gorontalo. In the implementation of this study, 3 respondents who were addicted to online games were taken at SMP Negeri 6 Gorontalo. The results of this case study show that the application of CBT can reduce addiction to online games. This is evidenced by 3 respondents before CBT was found to be addicted to online games in the moderate category and after using the CBT technique, 2 respondents experienced a decrease in addition to a mild category, and 1 respondent remained in the moderate category. The results obtained will be more effective if there is social support, parental control, and rewards.